Comparison between phenylephrine and ephedrine in preventing hypotension during spinal anesthesia for cesarean section - Iqra Nazir; Mubasher A Bhat; Syed Qazi; Velayat N Buchh; Showkat A Gurcoo (Wolters Kluwer Medknow Publications, 2012)
Background: Maternal hemodynamic changes are common during spinal anesthesia for cesarean delivery. Many agents are used for treating hypotension. In this study we compared the efficacy of ephedrine and phenylephrine in preventing and treating hypotension in spinal anesthesia for cesarean section and their effect on fetal outcome. Materials and Methods: A total of 100 ASA Grade I patients undergoing elective cesarean section under spinal anesthesia with a normal singleton pregnancy beyond 36 weeks gestation were randomly allocated into two groups of 50 each. Group I received prophylactic bolus dose of ephedrine 10 mg IV at the time of intrathecal block with rescue boluses of 5 mg. Group II received prophylactic bolus dose of phenylephrine 100 μg IV at the time of intrathecal block with rescue boluses of 50 μg. Hemodynamic variables like blood pressure and heart rate was recorded every 2 minutes up to delivery of baby and then after every 5 minutes. Neonatal outcome was assessed using Apgar score at 1 and 5 minutes and neonatal umbilical cord blood pH values. Results: There was no difference found in managing hypotension between two groups. Incidence of bradycardia was higher in phenylephrine group. The differences in umbilical cord pH, Apgar score, and birth weight between two groups were found statistically insignificant. Conclusion: Phenylephrine and ephedrine are equally efficient in managing hypotension during spinal anesthesia for elective cesarean delivery. There was no difference between two vasopressors in the incidence of true fetal acidosis. Neonatal outcome remains equally good in both the groups.